Feasibility, acceptability, and preliminary efficacy of yoga to improve maternal mental health and immune function during the COVID-19 crisis (Yoga-M2 trial): a pilot randomized controlled trial - Shidhaye, Rahul; Bangal, Vidyadhar; Bhargav, Hemant; Tilekar, Swanand; Thanage, Chitra; Gore, Suryabhan; Doifode, Akshada; Thete, Unnati; Game, Kalpesh; Hake, Vaishali; Kunkulol, Rahul (Frontiers in Human Neuroscience, 2023)
Women are vulnerable during pregnancy as they experience multiple physical and psychological problems which can lead to stress and poor quality of life ultimately affecting the development of fetus and their own health during and after pregnancy. Prior evidence suggests that pre-natal yoga can improve maternal health and well-being and can have beneficial effect on immune system functioning. No study till date has been conducted in a rural, low-resource setting in India to assess the feasibility, acceptability, and preliminary efficacy of a yoga-based intervention on perceived stress, quality of life, pro-inflammatory biomarkers, and symptoms of upper respiratory tract infections. Yoga-based intervention to improve maternal Mental health and iMmunity during the COVID-19 crisis (Yoga-M2 trial), a single-blind individual randomized parallel group-controlled pilot trial with 1:1 allocation ratio was implemented to address this gap. We randomly allocated 51 adult pregnant women, with gestational age between 12–24 weeks in the Yoga-M2 arm (n=25) or the enhanced usual care arm (EUC) (n=26). Three-months follow-up assessment was completed for 48 out of 51 participants (94.12%). Feasibility and acceptability were assessed using the process data and In-Depth Interviews (IDIs) with the trial participants and yoga instructors. Multiple linear regression was used to compare follow-up scores for quantitative outcomes. The key barriers to practice yoga were lack of knowledge about the benefits of yoga, lack of ‘felt need’ to practice yoga, lack of time to practice, lack of space, lack of transport, and lack of peer group to practice yoga. Despite of this, women who regularly practiced yoga described the benefits and factors which motivated them to practice regularly. We did not find any statistically significant difference between both arms in total Perceived Stress Scale scores, quality of life (Eq-5D-5L index), and serum C Reactive Protein levels at three-month follow-up assessment. The learnings from this trial will help design the explanatory trial in the future.